A Spiro Phosphamide Catalyzed Enantioselective Proton Transfer of Ylides in a Free Carbene Insertion into N−H Bonds - Pan, Jia‐Bin; Zhang, Xuan‐Ge; Shi, Yi‐Fan; Han, Ai‐Cui; Chen, Yu‐Jia; Ouyang, Jing; Li, Mao‐Lin; Zhou, Qi‐Lin (Angewandte Chemie International Edition, 2023)
Free carbene readily causes multiple side reactions due to its high energy, thus its asymmetric transformation is very difficult. We present here our findings of high‐pKa Brønsted acid catalysts that enable free carbene insertion into N−H bonds of amines to prepare chiral α‐amino acid derivatives with high enantioselectivity. Under irradiation with visible light, diazo compounds produce high‐energy free carbenes that are captured by amines to form free ylide intermediates, and then the newly designed high‐pKa Brønsted acids, chiral spiro phosphamides, promote the proton transfer of ylides to afford the products. Computational and kinetic studies uncover the principle for the rational design of proton‐transfer catalysts and explain how the catalysts accelerate this transformation and provide stereocontrol. A highly enantioselective free carbene insertion into the N−H bond of amines has been achieved. Newly designed high‐pKa Brønsted acid catalysts, chiral spiro phosphamides, were found to be key and promote the proton transfer of the ylide intermediates and control the enantioselectivity of the reaction. The reaction provides a new approach to amino acid derivatives.